PEMBENTUKAN KARAKTER MANDIRI ANAK USIA DINI MELALUI KEGIATAN RUTIN HARIAN DI TK NEGERI PEMBINA KOTA BAUBAU - Firji Hertuni; La Jeti; Rachman Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the process of developing independence character in early childhood through daily routine activities at TK Negeri Pembina Baubau City and to identify supporting and inhibiting factors. This research employed a qualitative approach with a case study design. Research subjects included the principal, teachers, and children aged 4–5 years. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman’s model through data reduction, data display, and conclusion drawing. The results showed that daily routine activities such as storing personal belongings, handwashing, eating together, tidying up play equipment, and classroom transition routines significantly contributed to developing children’s independence character. The developed aspects included self-help skills, responsibility, discipline, initiative, and self-confidence. Supporting factors included a conducive school environment, teacher consistency, positive reinforcement, and school programs, while inhibiting factors involved overprotective parenting, lack of consistency at home, and limited opportunities for independent decision-making. This study confirms that daily routine activities are effective strategies for character education in early childhood when consciously designed, structured, and consistently implemented. The findings highlight the importance of collaboration between schools and families in optimizing children’s independence character formation.